The Humanist Islam Concept in Ahmad Syafii Maarif’s Thought and Its Relevance to Indonesian Identity in the Post-Reform Era - Haq, Mochamad Ziaul (Integritas Terbuka: Peace and Interfaith Studies, 2025)
This study aims to analyze the integrative concept of Islamic humanism formulated by Ahmad Syafii Maarif in the context of Indonesian socio-political dynamics and religious pluralism. The research addresses the critical need to bridge Islamic values, Indonesian identity, and humanitarian ethics in response to the rise of religious exclusivism and secular-liberal tendencies. Employing a qualitative approach with a library research design, this study applies thematic coding to analyze primary texts by Syafii Maarif and relevant scholarly interpretations. The findings reveal that Syafii Maarif offers a paradigm of substantive Islam that harmonizes rationality, democracy, and social ethics while rejecting formalistic and doctrinaire approaches to religion. His thought draws inspiration from reformist figures such as Fazlur Rahman and Muhammad Iqbal, but is distinct in its contextual application within Indonesian democracy and civil society. The implications of this study suggest the need for a reorientation of Islamic discourse in Indonesia toward inclusivity, pluralism, and active citizenship. This research contributes to the development of Islamic thought by presenting a comprehensive and contextualized interpretation of Islam that affirms both national identity and universal humanitarian values. The originality of this research lies in its integration of philosophical, theological, and political dimensions within a single conceptual framework, offering new insights into the role of Islam in fostering democratic ethics and social cohesion in plural societies.